Colonic strictures in Crohn’s disease: a non-surgical survival - Sarra Laabidi; Hamed Aboubecrine; Salma Souissi; Donia Gouiaa; Asma Labidi; Nadia Ben Mustapha; Anis Haddad; Amine Sebai; Meriem Serghini; Monia Fekih; Hanene Jaziri; Jalel Boubaker (Future Science OA)
Background Colonic stenosis in Crohn’s disease (CD) is uncommon, and data on surgery-free survival are limited. This study aimed to determine surgery-free survival rates and identify associated factors.Patients and methods A retrospective study was conducted from 2003 to 2022, including patients with CD complicated by colonic stenosis. Patients with uncertain diagnoses or follow-up periods of less than six months were excluded.Results Fifty-six patients were included (median age 44 years [range 14-65], male-to-female ratio = 0.93). Surgery-free survival rates were 58.9% at 6 months, 43.7% at 2 years, and 31.7% at 5 years, with an average surgery-free survival of 46.7 months. Univariate analysis showed that joint manifestations (p = 0.01), corticosteroids (p = 0.02), anti-TNF alpha (p = 0.02), salicylates (p = 0.02), and azathioprine (p = 0.01) increased surgery-free survival. Complications such as collections or internal fistulas (p = 0.03), parietal ulceration on imaging (p = 0.01), and acute intestinal obstruction (p = 0.01) were associated with reduced surgery-free survival. In multivariate analysis, biologic therapy was the only independent protective factor against surgery (p = 0.001, OR = 0.19).Conclusion The early introduction of biologic therapy is crucial for increasing surgery-free survival in patients with colonic stenosis in CD, given the limited effectiveness of conventional treatments.